2009
DOI: 10.1007/s11605-008-0703-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy Tube Placement Is Safe in Patients Undergoing Corticosteroid Therapy

Abstract: Percutaneous endoscopic gastrostomy tube placement may be safely performed in patients receiving corticosteroids both acutely and chronically with complication rates comparable to those patients not receiving steroid medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…93,94 There seems to be no difference in complication rates between patients on steroids and those not on steroids. 95 In the pediatric population, there seems to be equal short-term safety for endoscopic PEGs and surgical gastrostomies with or without fundoplication. 96 There are conflicting data regarding the safety and an increased complication rate of PEG tube placement in children with ventriculoperitoneal shunts.…”
Section: Safetymentioning
confidence: 99%
“…93,94 There seems to be no difference in complication rates between patients on steroids and those not on steroids. 95 In the pediatric population, there seems to be equal short-term safety for endoscopic PEGs and surgical gastrostomies with or without fundoplication. 96 There are conflicting data regarding the safety and an increased complication rate of PEG tube placement in children with ventriculoperitoneal shunts.…”
Section: Safetymentioning
confidence: 99%
“…[1][2][3][4][5] Even though covering pull-type PEG tube or push-type method may prevent infection, the standard "pull method" is still the most widely used technique because it is well established. [5][6][7][8] In the procedure, the gastrostomy catheter will be passed through the mouth and oropharynx until reaching the abdominal wall.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, the safety of PEG tubes in human patients receiving corticosteroids was investigated, and it was concluded that this technique was not associated with an increased complication rate in patients receiving acute or chronic corticosteroid treatment . To the authors' knowledge, no studies have investigated the effect of corticosteroid treatment in veterinary patients concomitantly receiving enteral feeding by means of a PEG tube, and this, therefore, was the objective of this study.…”
mentioning
confidence: 99%